Windrush child - Zephaniah, Benjamin 1958-2023 (Scholastic, 2020)
Leonard is shocked when he arrives with his mother in the port of Southampton. His father is a stranger to him, it's cold and even the Jamaican food doesn't taste the same as it did back home in Maroon Town. But his parents have brought him here to try to make a better life, so Leonard does his best not to complain, to make new friends, to do well at school – even when people hurt him with their words and with their fists. How can a boy so far from home learn to enjoy his new life when so many things count against him?
Keywords: Geschichte 1950-2000; Jamaikanischer Jugendlicher; Familie; Auswanderung; Diskriminierung; Großbritannien; Immigrants / Juvenile fiction; Fiction 7+; Kinderbuch